Haematological response in the treatment of naturally acquired ectoparasite infestations in rabbits - W. Moonarmart (2019)
© WRSA, UPV, 2003. The objective of this study was to determine changes in haematological values of topical administration of selamectin in rabbits with at least one species of naturally acquired ectoparasite infestation (Sarcoptes scabiei var. cuniculi, Psoroptes cuniculi, or Cheyletiella spp). Thirty-five rabbits were enrolled. They underwent physical examination and assessment of ectoparasite infestations on days 0, 14, 28, 56 and 86. Blood for haematology and serum biochemistry was collected on days 0, 14, 28 and 56. Selamectin was topically applied at a dose of 15 mg/kg onto the skin on days 0, 14 and 28, respectively. No ectoparasites or eggs were found in these rabbits from day 28 onwards by skin scraping and/or tape cytology. Haematology and serum biochemistry values were within normal limit throughout the study. However, the neutrophil to lymphocyte ratio significantly decreased post-treatment from 2.89 (0.90-5.47) on day 0 to 1.38 (0.56-3.09), and 1.44 (0.42-4.47) on days 14 and 56, respectively. There were no adverse drug reactions or treatment-related mortalities during the study. This study indicated that selamectin was effective and safe in the treatment and prevent re-infestation for at least 58 d post-treatment. Moreover, the neutrophil to lymphocyte ratio could be used for monitoring of inflammatory response in rabbits.